UPAYA MENINGKATKAN HASIL BELAJAR IPS DAN MEMBENTUK KARAKTER SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SDN 060809 MEDAN - Nani Hariani Harahap (JURNAL TEMATIK, 2019)
This study aims to improve social studies learning outcomes and shape student character through the STAD type cooperative learning model at SDM 060809 Medan. This type of research is a Classroom Action Research conducted at SDN 060809 Medan with the subject of research being the fifth grade students totaling 22 people. The object of research is the application of the STAD Type Cooperative Learning Model to Improve Social Studies Learning Outcomes and Shape Student Character. The research data were obtained from the learning scenario, the Student Character Questionnaire Observation sheet, and the Student Learning Outcomes Test. The results of the validation of the device in the category (can be used with several revisions) and the results of the test instrument test have a reliability of 0.97 or very high. The study consisted of 2 cycles and the test was given at the end of each cycle. The results of data analysis in the second cycle obtained the results: (1) Formation of Character Students have met the specified percentage of 91%; (2) The learning achievement test score of 95.45% of the number of students who took the test was successful. Based on the results of the second cycle, it can be concluded that the application of the STAD Cooperative Learning Model can shape students' Character and Student Learning Outcomes. This success occurs with various revisions of action based on the results of reflection on the learning process and results.